2023
DOI: 10.1128/jb.00476-22
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Central Carbon Metabolism Increases β-Lactam Antibiotic Susceptibility in Vibrio cholerae

Abstract: Antibiotic tolerance (the ability to survive exposure to antibiotics) is a stepping stone toward antibiotic resistance (the ability to grow in the presence of antibiotics), an increasingly common cause of antibiotic treatment failure. The mechanisms promoting tolerance are poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Regulation of bacterial metabolism has been identified as an additional mechanism that supports antibiotic resistance in Vibrio and other species ( 83 - 85 ). Indeed, a recent work has demonstrated that NaCl negatively regulates proton motive force (PMF) in Vibrio alginolyticus , leading to a reduction in aminoglycoside uptake and a subsequent increase in antibiotic resistance at high salt ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of bacterial metabolism has been identified as an additional mechanism that supports antibiotic resistance in Vibrio and other species ( 83 - 85 ). Indeed, a recent work has demonstrated that NaCl negatively regulates proton motive force (PMF) in Vibrio alginolyticus , leading to a reduction in aminoglycoside uptake and a subsequent increase in antibiotic resistance at high salt ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…This process provides precursors for all the biosynthetic reactions that are required for cell survival [66,67]. This makes central carbon metabolism i.e., carbon uptake and carbon utilization, an attractive antimicrobial target because these processes are typically essential for microbial survival [68][69][70]. Innate immunity, which frequently deprives bacteria of iron, amino acids, and other essential nutrients, serves as an example of the efficacy of this strategy [71][72][73].…”
Section: Central Carbon Metabolismmentioning
confidence: 99%
“…Next, we set out to evaluate cell shape and cell differentiation as previous studies have reported that dysregulated central carbon metabolism often leads to defects in cell morphology [38,39]. Moreover, for growth on chitinaceous sources, V. parahaemolyticus is known to exhibit elongated cell morphologies as a response to environmental cues [21].…”
Section: Hexr Is a Regulator For Biofilm Formation Cell Differentiati...mentioning
confidence: 99%
“…Microscopy was performed as previously described [38], with minor adjustments. Overnight cultures were inoculated into LB and MM9 at a starting 𝑂𝐷 600𝑛𝑚 of 0.025 for 16 hours at 37C, 200rpm.…”
Section: Microscopymentioning
confidence: 99%